STUDY OF AWARENESS OF SECONDARY LEVEL TEACHERS TOWARDS DISASTER MANAGEMENT AND RELIEF PROGRAMS - Saini, Naveen Kumar; Sengar, Kalpana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of this study was to study the awareness of secondary level teachers towards disaster management and relief programs. Survey method has been used in this study. 200 teachers studying in government schools of Jaipur district have been selected for the sample. In the presented research study, self-made disaster management awareness scale and disaster relief program awareness scale have been used. The data has been analyzed through mean, standard deviation and t-test. In the conclusion of the study, it was found that there is no significant difference in the awareness of secondary level female and male teachers towards disaster management and relief programs.